Options and the Bubble - BATTALIO, ROBERT; SCHULTZ, PAUL (Journal of Finance, 2006)
ABSTRACT Many believe that a bubble existed in Internet stocks in the 1999 to 2000 period, and that short‐sale restrictions prevented rational investors from driving Internet stock prices to reasonable levels. In the presence of such short‐sale constraints, option and stock prices could decouple during a bubble. Using intraday options data from the peak of the Internet bubble, we find almost no evidence that synthetic stock prices diverged from actual stock prices. We also show that the general public could cheaply short synthetically using options. In summary, we find no evidence that short‐sale restrictions affected Internet stock prices.